Patterns of lipid‐injectable emulsion use in neonatal intensive care units across the United States: A multi‐institution survey. Issue 1 (16th July 2022) - Huff, Katie A.; Nayak, Sujir Pritha; Ahmad, Irfan; DiGeronimo, Robert; Hair, Amy; Kim, Jae H.; Markel, Troy; Piazza, Anthony; Reber, Kristina; Roberts, Jessica; Sharma, Jotishna; Sullivan, Kevin; et al.
Abstract: Background: Lipid‐injectable emulsions (ILEs) are a necessity for neonates dependent on parenteral nutrition (PN). In this manuscript, we describe the patterns of ILE use in neonatal intensive care units (NICUs) in the United States (US). Methods: An electronic survey was sent to 488 NICUs across the US between December 2020 and March 2021. Survey fields included availability and utilization of various ILE in neonates. Results: The response rate was 22% (107 out of 488). Soybean oil ILE (SO‐ILE) and soybean oil, medium‐chain triglycerides, olive oil, fish oil ILE (SO, MCT, OO, FO‐ILE) had similar availability (87% vs 86%, respectively), and SO, MCT, OO, FO‐ILE was more commonly used (SO‐ILE, 71% vs SO, MCT, OO, FO‐ILE, 86%). Fish oil‐ILE (FO‐ILE) was used by 55% of centers. SO‐ILE was most frequently used with PN and needs <4 weeks without cholestasis (79%). The most common reason for SO, MCT, OO, FO‐ILE use was cholestasis (71%). ILE minimization was used by 28% of SO‐ILE and 22% of SO, MCT, OO, FO‐ILE users; 95% of these centers restrict SO, MCT, OO, FO‐ILE to doses ≤2 g/kg/day. Twenty‐two percent of centers started FO‐ILE at direct bilirubin of >5 mg/dl. Conclusion: The results of this survey reveal significant variability in ILE usage across the US. Lipid minimization with SO, MCT, OO, FO‐ILE and initiation of FO‐ILE for cholestasis at higher bilirubin thresholds are prevalent. Such reports are crucial for a better understanding of ILE use in the NICU and in future ILE development.